If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1x = -6 Solving 3 + -1x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = -6 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = -6 + -3 -1x = -6 + -3 Combine like terms: -6 + -3 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9
| 35x=16 | | 10t^2+33t-54=0 | | 2+5(x-3)-(-3+x)(2x+5)= | | 4y-8x=32 | | 9*3-4+27/9-2= | | 2(x+7)=6(-8) | | 28x=16 | | 62-7x=2x+20 | | 3x^2=2(x+2) | | -(-9y+3)-5=-5-y | | 41-6x=23 | | f(x)=4x-10 | | 2(0)=-2(0) | | x^2=27i | | 5x+6=66 | | 6y+20=-5+4y | | 2(x)=-2x | | 0.5x=2000 | | 66x-4x^2-272=0 | | 5x+6x+7x=180 | | f(x)=-7x+5 | | f(x)=-2x | | 5x+1=123 | | 4x^5-324x=0 | | f(x)=5x^2-12 | | 5a^3(25b-a)/a-25b | | 6w=7w-5 | | 4x+6=2x+6 | | 25b-a/a-25b | | 4x^2+58x-272=0 | | 1z=50 | | 3y=50 |